NIMG-11. VOLUMETRIC ENDPOINTS IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG): COMPARISON TO CROSS-SECTIONAL MEASURES AND CORRELATION WITH OUTCOMES. (12th November 2021) - Lazow, Margot; Nievelstein, Martijn; Lane, Adam; Bandopadhayay, Pratiti; DeWire-Schottmiller, Mariko; Fouladi, Maryam; Glod, John; Greiner, Robert; Hoffman, Lindsey; Hummel, Trent; Kilburn, Lindsay; Leary, Sarah; et al.
Abstract: INTRODUCTION: Cross-sectional tumor measures are used as endpoints in clinical trials of DIPG, but may not capture meaningful changes in disease burden. Volumetric measures may provide a more accurate assessment of tumor growth. We measured the correlation between cross-sectional and volumetric measures and compared their prognostic impact to better understand response evaluation in DIPG. METHODS: Patients from the International DIPG Registry with diagnostic and post-radiation MRIs were included. Utilizing mint Lesion TM software, tumors were manually contoured by an experienced pediatric neuro-radiologist to extrapolate cross-sectional product (CP) and volume measures. Correlation between CP and volume was assessed by linear regression. Landmark analyses were performed to determine differences in overall survival (OS) (via log-rank) between patients classified as progressive disease (PD) versus non-PD according to CP and volumetric measurements at one-, three-, and five-months post-radiation. Imaging consistent with pseudoprogression was designated non-PD. Hazard ratios (HR) for survival after these timepoints were calculated by Cox regression. RESULTS: A total of 317 MRIs from 46 patients were analyzed. When comparing change from smallest previous tumor size, CP increase of 25% (PD by RAPNO) correlated with volume increase of 28% (R 2 =0.685). There was no difference in OS between patients classified as PD versus non-PD by CP at one-month, three-months, or five-months post-radiation (p >0.05). However, significant differences in OS were observed between patients classified as PD versus non-PD by volume (28% increase) at one-month (2.7 vs. 12.8 months, p=0.005), three-months (1.9 vs. 10.7 months, p=0.036), and five-months post-radiation (3.7 vs. 9.1 months, p=0.023). PD by volume, but not by CP, was predictive of survival at all timepoints (HR: 5.0, 2.4, 2.4). CONCLUSIONS: Volumetric assessments of PD correlated better with survival than CP at all post-radiation timepoints. Tumor volume likely represents a more accurate, prognostically-relevant measure of disease burden that deserves investigation in future DIPG trials.